“I Didn’t Feel I Was A Victim”: A Phenomenological Analysis of the Experiences of Male-on-male Survivors of Rape and Sexual Abuse - Widanaralalage, B. Kennath (Victims & offenders, 2022)
Research on men’s experiences of sexual victimization is limited and largely outdated. The present study seeks to remedy this issue by qualitatively examining the accounts of nine male-on-male survivors of rape and sexual abuse in the UK. It examines survivors’ experiences of psychological distress post-incident, the influence and manifestation of male rape myths, challenges in self-recognition and disclosure, and barriers to accessing therapeutic support and reporting to the Criminal Justice System (CJS). Participants took part in one-to-one, semi-structured video interviews, and an interpretative phenomenological analysis (IPA) was utilized to identify four superordinate themes of participants’ experiences: i) gendered narratives, ii) coping with the abuse, iii) masculinity, and iv) reporting to the police. These themes emphasized the stigma and hostility repeatedly encountered by survivors after their victimization. Participants provided an account of short and long-term psychological issues following the abuse, emphasizing the role of self-perceptions of masculinity in the development of unhealthy coping mechanisms. Findings also highlighted the prevalence of prejudice and rape mythology that characterized negative encounters within the public, voluntary agencies, and the CJS. Results are discussed in relation to current service provision in the UK, recommendations for future research, and avenues for improvements across multiple vital entry points.